Imagined states : nationalism, utopia, and longing in oral cultures - Del Giudice, Luisa; Porter, Gerald, 1946- (Utah State University Press, 2001)
An international ensemble of folklore scholars looks at varied ways in which national and ethnic groups have traditionally and creatively used imagined states of existence--some idealizations, some demonizations--in the construction of identities for themselves and for others.